Interrogating the academy: renegotiating the terms of discourse - Heredia, Rudolf C. (2016)
The challenge is to become organic intellectuals. For middle-class academics and activists, who are alienated from the grass-roots people in the field, this is a difficult and delicate task. An organic intellectual is someone who can catalyse and articulate the experience of the people, voice their knowledge, echo their wisdom, and make them present in places where they are not heard or acknowledged. - Reproduced.
Keywords: Intelligentsia